2007
DOI: 10.1186/1749-7922-2-23
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of haemoperitoneum in ectopic pregnancy: derivation of a prediction model

Abstract: Background: To derive an ultrasound-based prediction model for the quantification of haemoperitoneum in ectopic pregnancy (EP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
1
26
0
3
Order By: Relevance
“…A detailed description of the standardized sonograms has been reported elsewhere [19]. Ultrasound variables of hemoperitoneum were considered to be positive when the pelvic intra-peritoneal effusion exceeded the uterine fundus or was found around the ovary [13,20], or abdominal effusion was visible in Morison pouch [10,11]. All patients had ultrasonography while in the emergency unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the standardized sonograms has been reported elsewhere [19]. Ultrasound variables of hemoperitoneum were considered to be positive when the pelvic intra-peritoneal effusion exceeded the uterine fundus or was found around the ovary [13,20], or abdominal effusion was visible in Morison pouch [10,11]. All patients had ultrasonography while in the emergency unit.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous retrospective explanatory study [13], a clinical model was developed to predict abundant hemoperitoneum on the basis of 3 criteria: spontaneous moderate-to-severe pelvic pain; fluid above the uterine fundus or around the ovary at TVUS; and a serum hemoglobin concentration of less than 10 g/dL. However, that study did not take into account the physical examination, which has previously been found to be useful for the diagnosis of hemoperitoneum in EP [14].…”
Section: Introductionmentioning
confidence: 99%
“…La première urgence à éliminer est l'existence d'un hémopéritoine massif compliquant une grossesse extra-utérine et mettant en jeu le pronostic vital [14]. La torsion d'annexe constitue également une urgence compte tenu du pronostic fonctionnel engagé de l'annexe tordue [15].…”
Section: Quels Sont Les Objectifs De L'examen éChographique Aux Urgenunclassified
“…Dans un contexte de grossesse précoce, le balayage nécessaire à la réalisation correcte de ce cliché permettra de localiser une éventuelle grossesse intra-utérine ou au contraire de mettre en évidence une vacuité utérine ou une anomalie (grossesse arrêtée, oeuf clair, rétention de tissu trophoblastique ou môle hydatiforme). De plus, si le fond et le col sont bien visibles, une analyse semi-quantitative d'un épanchement liquidien ou sanglant intrapelvien est réalisable à partir de ce cliché, ce qui est particulièrement intéressant pour quantifier un éventuel hémopéritoine [14]. En dehors d'une grossesse, la réalisation de ce cliché permet l'analyse de l'endomètre (épaisseur, présence d'un polype) et du myomètre (présence de myomes ou adénomyose) ; un cliché de chaque ovaire.…”
Section: Clichés éChographiques Réalisésunclassified
See 1 more Smart Citation